Efektivitas Alat Peraga Mobil Jet Udara Untuk Menumbuhkan Minat Belajar Dasar-Dasar Sains Siswa Sekolah Dasar - I Ketut Mahardika; Singgih Baktiarso; Dewi Kumala Sari; Djurmiya Djurmiya; Putri Ratu Ardiya; Linda Nadia Luffianti; Fitriya Ichda Setiawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Studying the natural sciences is the task of the students. Science learning requires active student learning related to physical or mental activity. The purpose of learning science for children is to develop children's development and potential. In addition, the purpose of scientific learning is to develop individuals to become familiar with the field of science and develop the ability to use basic aspects to solve the problems they face. in learning. Scientific Basis of Elementary School Students The results showed that there were differences in students' understanding between source-based and non-source-based learning, based on supporting information in the form of observation, source-based learning, and between respondents in elementary schools. primary. school age, clearly learning with visual aids is more effective and easy to understand.